Предмет: Алгебра,
автор: sed81
Упростите выражения
(буду очень благодарен)
a + b + (-а) + (-b) + (-b) =
-a + (-а) + b + a+ (-b) =
-а + (-а) + (-а) +b +b +(-b) =
Ответы
Автор ответа:
1
Ответ:
Объяснение:
a + b + (-а) + (-b) + (-b) = а + b - a - b - b= -b
-a + (-а) + b + a+ (-b) = -a-a + b + a -b= -a
-а + (-а) + (-а) +b +b +(-b) = -a -a - a +b+b - b= -3a+b
Похожие вопросы
Предмет: Литература,
автор: dux22873535
Предмет: Другие предметы,
автор: Track7
Предмет: Геометрия,
автор: Benson01
Предмет: История,
автор: IReysiI
Предмет: Химия,
автор: Hello12387